Aprendizagem de tópicos de física moderna e contemporânea no ensino médio profissionalizante utilizando arduino - Bandeira, Sergilanio Lima (Universidade Federal Rural do Semi-Árido, 2017)
Nowadays students generally have permanent contact with technologies that are based on the Physics developed from the end of the 19th century to the present day, which in this work will receive the denomination of Modern and Contemporary Physics (FMC). As an example, we can mention plasma televisions, LCD and LED, photoelectric sensors used in computer and mobile processors among others. Physics teaching needs to account for students' curiosity about the physical principles that govern the operation of these technologies, requiring that new ways of approach be considered, given the complexity of inserting these themes in high school. As an alternative, this work proposes the use of Arduino, an open source and low cost platform, in experiments that aim to introduce FMC topics in high school. The topics chosen are: the photoelectric effect, the emission of radiation through the bodies, the dual behavior of light, and a discussion of semiconductor materials. It is not a didactic sequence to be developed in a set of classes, but of workshops in which experiments are carried out in order to prepare and motivate the student to study such topics. Initially the proposal was elaborated with the objective of being applied in the courses of Computer and Computer Networks of the professional schools of the state of Ceará, however its application allowed to conclude that it can be developed in any secondary school. Theoretical contribution in this work was the premises that govern professional education, Ausubel's theory of meaningful learning and the concept of active learning methodology, which is very widespread today, in which the student assumes the central role in the construction of knowledge . The proposal does not replace the class, but proposes potentially significant experiments with the intention of acting as a previous organizer (see theoretical framework) motivating and preparing the students to study the topics addressed in order to facilitate a more meaningful learning of the contents, thus improving the quality of teaching and attracting more young people to the study of physics. The analysis of the results obtained from the answers given by the students to the evaluation questionnaire allowed to conclude that the proposal reached its objectives, since they demonstrated to have acquired knowledge that could facilitate a learning of the contents when treated in the classroom. It was also possible to perceive that proposals that use experiments allied to technological resources allowing the visualization and understanding of technologies present in our daily life are very well accepted by the students. It is clear that placing the student as the protagonist of the process has a very positive effect on motivation and learning. Moreover, the ease in the development of the proposal showed that it is easily replicable and is expected to contribute to the improvement of physics teaching in general
Keywords: Física moderna e contemporânea; Aprendizagem significativa; Aprendizagem ativa; Experimentos; Arduino; Modern and contemporary physics; Meaningful learning; Active learning; Experiments; Arduino; CIENCIAS EXATAS E DA TERRA::FISICA